Konsumsi Bahan Bakar Akibat Buka Tutup Arus Lalu Lintas pada Jalan. Jl. Bts. Kota Lhokseumawe, Aceh Utara – Lhoksukon Km. 280 Provinsi Nanggroe Aceh Darussalam - Endang Widjajanti; Muhammad Iqbal (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
This study aims to determine the effect of vehicle queues on fuel consumption due to the opening and closing of traffic flows caused by drainage channels project throughout October 2020 on. Jalan. Bts. Lhokseumawe City/North Aceh – Lhoksukon Km. 280. The queue length analysis was calculated based on vehicle traffic flow in locations that have not been affected by the existence of open/close traffic flow activities and analysis of fuel consumption based on the length of delay and the number of vehicle queues using LAPI-ITB formula. The results showed that the queue of vehicles due to opening and closing of vehicle lanes for 6 hours (12.00 – 18.00 WIB) on holidays was 23% larger than the queue on weekdays. Vehicle queues for 6 hours on holidays cause additional vehicle fuel consumption for light vehicles (LV) of 424,15 liters, heavy vehicles (HV) of 53,09 liters, and motorcycles (MC) of 203,24 liters and on weekdays causes additional fuel consumption for light vehicles (LV) as much as 342,66 liters, Heavy vehicles (HV) as much as 35,85 liters, and motorcycles (MC) as much as 203,24 liters. Loss of fuel use due to queues caused by opening and closing roads on Jalan. Bts. Lhokseumawe City/North Aceh – Lhoksukon Km. 280 for 6 hours (12.00 – 18.00 WIB) on weekdays is 4.402.185,00 and on holidays it is Rp. 5.541.065,00.